Citicoline Modifies the Expression of Specific miRNAs Related to Cardioprotection in Patients with ST-Segment Elevation Myocardial Infarction Subjected to Coronary Angioplasty - Alejandro Silva-Palacios; Miguel Arroyo-Campuzano; Mirthala Flores-García; Mariana Patlán; Adrián Hernández-Díazcouder; Diego Alcántara; Ixchel Ramírez-Camacho; Dana Arana-Hidalgo; Elizabeth Soria-Castro; Fausto Sánchez; Héctor González-Pacheco; Cecilia Zazueta (MDPI AG, 2022)
Extracellular vesicles are recognized as signaling mediators between cells both in physiological and pathological communication. In this work, we explored the potential effect of citicoline to modify relevant proteins or miRNAs for cardioprotection in the smallest population of such microvesicles; i.e., in exosomes from patients diagnosed with ST-segment elevation myocardial infarction (STEMI) undergoing coronary angioplasty. The plasma-exosome-enriched fraction from these patients was characterized. Their cellular origin was assessed by flow cytometry and Western blot, whereas miRNA expression was evaluated by real-time polymerase chain reaction (qRT-PCR). The content of caveolin-1, caveolin-3, and hnRNPA2B1, which play a relevant role in selective transport of miRNAs into microvesicles, along with the effect on cell viability of the exosomes obtained from citicoline-treated and untreated groups were also analyzed. Our results showed that hypoxic stress increases exosome release into the circulation. Moreover, we found that CD146+ increased in exosomes from citicoline-treated patients, while CD142+ decreased in these patients compared to the placebo group. No changes were detected in the protein levels of caveolin-1, caveolin-3, and hnRNPA2B1. Citicoline administration modified the expression of miR233-3p, miR92, and miR21-5p in exosomes. Cell viability decreased in the presence of exosomes from infarcted patients, while incubation of H9c2 cells with exosomes from patients reperfused with citicoline did not affect cell viability. In conclusion, citicoline administration modifies the expression of specific miRNAs related to cardioprotection in exosomes.